The outcome of two SMA cases treated with nusinersen at seven hours and at three days of life: the earliest ever - ÜNVER, OLCAY; ESİM BÜYÜKBAYRAK, ESRA; GÖKDEMİR, YASEMİN; MEMİŞOĞLU, ASLI (My University, 2022)
New molecular therapies are available for the treatment of spinal muscular atrophy (SMA) but early intervention is required. We report two cases that were diagnosed prenatally, where treatment with nusinersen was initiated within 7 h and three days respectively. The children were followed up for 13 months and almost six years respectively. Both children have developed within entirely normal centiles, indicating that initiating treatment immediately after birth, as in these cases, is essential for a good outcome.
Keywords: Tıp; Dahili Tıp Bilimleri; Nöroloji; Yaşam Bilimleri; Sağlık Bilimleri; Temel Bilimler; Medicine; Internal Medicine Sciences; Neurology; Life Sciences; Health Sciences; Natural Sciences; KLİNİK NÖROLOJİ; Klinik Tıp; Klinik Tıp (MED); SİNİR BİLİMİ; Sinirbilim ve Davranış; Yaşam Bilimleri (LIFE); CLINICAL NEUROLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); NEUROSCIENCES; NEUROSCIENCE & BEHAVIOR; Life Sciences (LIFE); Duyusal Sistemler; Gelişimsel Sinirbilim; Bilişsel Sinirbilim; Hücresel ve Moleküler Sinirbilim; Sinirbilim (çeşitli); Genel Sinirbilim; Nöroloji (klinik); İnsan Bilgisayar Etkileşimi; Fizik Bilimleri; Sensory Systems; Developmental Neuroscience; Cognitive Neuroscience; Cellular and Molecular Neuroscience; Neuroscience (miscellaneous); General Neuroscience; Neurology (clinical); Human-Computer Interaction; Physical Sciences; Early treatment; Spinal muscular atrophy; THERAPY; Early treatment; Spinal muscular atrophy